2019 IEEE/CVF International Conference on Computer Vision (ICCV) 2019
DOI: 10.1109/iccv.2019.00149
|View full text |Cite
|
Sign up to set email alerts
|

Moment Matching for Multi-Source Domain Adaptation

Abstract: Conventional unsupervised domain adaptation (UDA) assumes that training data are sampled from a single domain. This neglects the more practical scenario where training data are collected from multiple sources, requiring multi-source domain adaptation. We make three major contributions towards addressing this problem. First, we collect and annotate by far the largest UDA dataset, called DomainNet, which contains six domains and about 0.6 million images distributed among 345 categories, addressing the gap in dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
1,008
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,255 publications
(1,022 citation statements)
references
References 29 publications
7
1,008
0
7
Order By: Relevance
“…For supervised DA between multiple H&E stained images, Tellez et al, [82] showed that mitosis-detection and cancer tissue classification in a particular color space leads to higher accuracy. Typically, to assess domain relationship and DA direction, it is necessary to use (a) large-scale empirical studies such as [6,58] exploring bi-directional DA across multiple datasets, (b) a representation-shift metric [24] to roughly quantify the risk of applying learned-representations from a particular domain to a new domain, or (c) multi-source DA [83], which automatically explores latent source domains in multi-source datasets and quantifies the membership of each target sample. However, such experimentation requires extensive benchmarking studies that are lacking in medical imaging.…”
Section: Domain Selection and Direction Of Domain Adaptationmentioning
confidence: 99%
“…For supervised DA between multiple H&E stained images, Tellez et al, [82] showed that mitosis-detection and cancer tissue classification in a particular color space leads to higher accuracy. Typically, to assess domain relationship and DA direction, it is necessary to use (a) large-scale empirical studies such as [6,58] exploring bi-directional DA across multiple datasets, (b) a representation-shift metric [24] to roughly quantify the risk of applying learned-representations from a particular domain to a new domain, or (c) multi-source DA [83], which automatically explores latent source domains in multi-source datasets and quantifies the membership of each target sample. However, such experimentation requires extensive benchmarking studies that are lacking in medical imaging.…”
Section: Domain Selection and Direction Of Domain Adaptationmentioning
confidence: 99%
“…Besides the marginal distributions, the output class distributions are also considered in domain adaptation [17]. In addition, multi-domain adaptation can be achieved through moment matching [18][19].…”
Section: Related Workmentioning
confidence: 99%
“…MDI3D: Two popular datasets, i.e., MI3DOR [24] and DomainNet [37], are used to collect samples for MDI3D [45]. We manually choose the common 16 classes from two datasets.…”
Section: Experiments 41 Datasetmentioning
confidence: 99%
“…We manually choose the common 16 classes from two datasets. 2D images are from three domains, including real images (from MI3DOR), sketch images (from DomainNet [37]) and quick draw images (from Do-mainNet [37]). The 3D objects are from MI3DOR [24].…”
Section: Experiments 41 Datasetmentioning
confidence: 99%
See 1 more Smart Citation